POSSIBILITIES OF PLUM CULTIVATION IN THE REPUBLIC OF SERBIA - Matković, Milutin (Economics of Agriculture, 2015)
Cultivation od plums has always been one of the most important parts of Serbian agriculture. In modern Serbian history cultivation of plums is among main parts of its economy, being one of the frst export products of modern Serbia. Agriculture is marked as one of the motors of revitalization of Serbian economy. Plum is the most common Serbian fruit species. Serbia is in top fve countries with area under plum. Western Europe has biggest market for plum and products of plum in the world. Serbian plum export is insignifcant. Serbia has the potential to become a regional leader in plum export. Variable results in plum cultivation states the plum cultivation needs modernization in every aspect in order to achieve modern level of cultivation of plums. In order to revive plum cultivation and make it proftable for export, comperhensive action which includes all relevant factors is nededed. This article will try to give insight in state of cultivation of plums and suggest posible guidelines in its revitalization.